RF Characterization of Intracellular Microalgae Lipids. (2016) - Fellahi, A. El; Bore, T.; Bodenes, P.; Bensalem, S.; Le Pioufle, B.; Lopes, F.; Martincic, E.; Français, O.
Abstract: This work presents an original approach to sense the lipid intracellular content of microalgae, by the Radio Frequency (RF) dielectric spectral characterization of these unicellular organisms. To do so, a "homemade" open-ended coaxial sensor was associated to a Vector Network Analyzer (VNA), which allowed a broadband characterization in the frequency range from 30MHz to 3GHz. The sensor combines a coaxial line with a modified SMA connector. This study shows that the lipid quantification can be determined with the complex dielectric spectra properties extracted from the reflection coefficient ( S 11 ) measurement. A calibration of the open-ended coaxial probe is performed by using three different conditions (vacuum, water, methanol) from which the complex dielectric behavior is mastered. A model inversion is finally achieved to estimate the complex permittivity spectrum of the biological samples in a large frequency range, which is related to the microalgae lipid content.